2021
DOI: 10.1542/peds.2020-049602
|View full text |Cite
|
Sign up to set email alerts
|

Prospect of Direct Benefit in Pediatric Trials: Practical Challenges and Potential Solutions

Abstract: Clinical research in pediatric patients is necessary to develop safe and effective medicines for children. US Food and Drug Administration (FDA) human subject protection regulations (21 Code of Federal Regulations 50, subpart D) require that, with limited exceptions, research in children that exceeds a defined level of risk must offer a prospect of direct benefit to the individual child that is sufficient to justify those risks. Growing attention to the merits of initiating pediatric clinical trials earlier in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Nonetheless, there is growing recognition of the merits and feasibility of initiating pediatric trials earlier. Recent methodologic advancements in pediatric extrapolation, pharmacokinetic and pharmacodynamic modeling, and adaptive trial designs, can be applied to support earlier initiation of pediatric trials . As part of planning efforts for future public health responses, appropriate trial designs should be identified to prioritize earlier and broader inclusion of children in clinical trials to ensure timely access to therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there is growing recognition of the merits and feasibility of initiating pediatric trials earlier. Recent methodologic advancements in pediatric extrapolation, pharmacokinetic and pharmacodynamic modeling, and adaptive trial designs, can be applied to support earlier initiation of pediatric trials . As part of planning efforts for future public health responses, appropriate trial designs should be identified to prioritize earlier and broader inclusion of children in clinical trials to ensure timely access to therapies.…”
Section: Discussionmentioning
confidence: 99%
“…We considered dose selection a crucial element of this trial, both for safety reasons but also to ensure prospect of direct benefit to participants. Broadly accepted ethical standards for clinical research in children require potential for direct benefit if participation leads to more than minimal risk ( 37 ), and thus Phase 1 dose-finding and pharmacokinetic ‘ADME’ (absorption, distribution, metabolism and elimination) studies are not considered appropriate. Moreover, whilst in the range of auto-immune and auto-inflammatory conditions, for which anakinra is indicated, dose is titrated to clinical response, no such clinical measure for titration exists for the indication of early-life inflammation in premature infants.…”
Section: Methods and Analysismentioning
confidence: 99%
“…37 38 In addition, the FDA human subject protection regulations clearly stipulate that pediatric clinical trials can only be conducted when the benefits outweigh the risks, or there is sufficient evidence to prove that the risks are reasonable and provide the prospect of direct benefit to children. 35 Due to the paucity of evidence regarding drugs intended for use in children the many differences between children and adults, it is difficult to define this 'direct benefit'. A workshop convened in 2019 by the FDA in collaboration with the Duke-Margolis Center for Health Policy produced expert journals.sagepub.com/home/taw Volume 14…”
Section: Use Of Medication In the Child Patientmentioning
confidence: 99%